2021
DOI: 10.1038/s41418-021-00784-1
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal microbiota influences clinical outcome and side effects of early breast cancer treatment

Abstract: The prognosis of early breast cancer (BC) relies on cell autonomous and immune parameters. The impact of the intestinal microbiome on clinical outcome has not yet been evaluated. Shotgun metagenomics was used to determine the composition of the fecal microbiota in 121 specimens from 76 early BC patients, 45 of whom were paired before and after chemotherapy. These patients were enrolled in the CANTO prospective study designed to record the side effects associated with the clinical management of BC. We analyzed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
97
1
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(111 citation statements)
references
References 61 publications
(70 reference statements)
5
97
1
8
Order By: Relevance
“…The study showed some similar findings of the potential use of the microbiome as a prognostication biomarker, and the potential of altering breast cancer into a tumour-infiltrating lymphocyte (TIL)-enriched tumour microenvironment, thus making it amenable to ICI therapy. This study [167] also elucidated other potential roles of the microbiome that have not been discussed above concerning PDAC. In this study, they have found other predictive biomarker roles of the microbiome, predictive of neurological treatment side effects and the potential to be utilised as a predictive tool of the efficacy of neoadjuvant and adjuvant chemotherapy [167].…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…The study showed some similar findings of the potential use of the microbiome as a prognostication biomarker, and the potential of altering breast cancer into a tumour-infiltrating lymphocyte (TIL)-enriched tumour microenvironment, thus making it amenable to ICI therapy. This study [167] also elucidated other potential roles of the microbiome that have not been discussed above concerning PDAC. In this study, they have found other predictive biomarker roles of the microbiome, predictive of neurological treatment side effects and the potential to be utilised as a predictive tool of the efficacy of neoadjuvant and adjuvant chemotherapy [167].…”
Section: Discussionmentioning
confidence: 59%
“…This study [167] also elucidated other potential roles of the microbiome that have not been discussed above concerning PDAC. In this study, they have found other predictive biomarker roles of the microbiome, predictive of neurological treatment side effects and the potential to be utilised as a predictive tool of the efficacy of neoadjuvant and adjuvant chemotherapy [167].…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…All mice were housed in sawdust-lined cages with constant temperatures (22–25°C) and suitable humidity (50 ± 2.0%). When the tumor (volume (mm 3 ) = length * width 2 /2) grew to approximately 600 mm 3 , the tumor-bearing mice were randomly divided into 5 groups (n =8): normal saline (NS), DOX (1.2 mg/kg), DOX+siMDR1 (contain 1.2 mg/kg DOX and 0.8 μg/kg siRNA), H/D (contain 1.2 mg/kg DOX), H/D/M (contain 1.2 mg/kg DOX) and C-H/D/M (contain 1.2 mg/kg DOX). Then once every other day via intravenous injection the mice were treated with their corresponding therapeutic regimen or NS.…”
Section: Methodsmentioning
confidence: 99%
“…Breast cancer is the most common cause of death and one of the most prevalent cancers among women worldwide. 1 , 2 As people pay more and more attention to cancer, the treatment strategies for tumors are gradually increasing, including surgery, chemotherapy, immunotherapy, and other methods. Studies have shown that phototherapeutic or chemotherapeutic nano-delivery systems can reduce metastasis through enhanced tumor-killing efficiency.…”
Section: Introductionmentioning
confidence: 99%